Concept of Satvapatana: a review - Hussain, Gazala (Journal of Drug Delivery and Therapeutics, 2019)
Rasashastra is a branch in Ayurveda that deals with Ayurveda Pharmaceutics using drugs of varied origin like metals, minerals, gemstones, mercury, etc. Indian alchemy consists of various processes like shodhana (purification), marana (incineration), amrutikarana (processing the incinerated ash to imbibe more qualities), etc. One among these processes is Satvapatana (extraction of essence from mineral ores). Satvapatana is a process where the mineral ore mentioned in texts of Indian alchemy are mixed with other drugs and subjected to heat by which the essence of the ore is obtained.  The satva of the drugs are of different colours and different types of heat are mentioned to extract the satva for different minerals based on the hardness of the drug. These satvas are used in different processes of Mercury and also in therapeutics.Keywords: Satvapatana, rasashastra, satva, minerals, mercury